2008
DOI: 10.1158/0008-5472.can-08-0839
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase-2A Is a Target of Epigallocatechin-3-Gallate and Modulates p53-Bak Apoptotic Pathway

Abstract: Abstract(-)-Epigallocatechin-3-gallate (EGCG) is a well-known chemoprevention factor. Recent studies have revealed that EGCG triggers cancer cells undergoing apoptosis through p53-dependent pathway. How EGCG activates p53-dependent apoptosis is not fully understood. In the present study using JB6 cell as a model system, we have shown that EGCG can negatively regulate protein serine/threonine phosphatase-2A (PP-2A) to positively regulate p53-dependent apoptosis. First, EGCG at physiologic levels down-regulates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
68
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 45 publications
1
68
1
1
Order By: Relevance
“…5 PP-2A is also found to modulate the phosphorylation status of p53 at these sites to suppress stress-induced apoptosis. 6,7 In this study, we present the first evidence to show that PP-1 has a critical role during the activation process of Akt1 signaling pathway.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…5 PP-2A is also found to modulate the phosphorylation status of p53 at these sites to suppress stress-induced apoptosis. 6,7 In this study, we present the first evidence to show that PP-1 has a critical role during the activation process of Akt1 signaling pathway.…”
mentioning
confidence: 68%
“…After dephosphorylation, the free 32 P released from substrate proteins by PP-1 or PP-2A was measured in a scintillation counter. As shown in Figure 2c, in vitro enzyme concentration-dependent assays showed that PP-1 was more efficient than PP-2A in dephosphorylating the labeled substrate with the same amount of enzyme (PP-1 and PP-2A activities were calibrated as described previously 5,6 ). Similarly, time-dependent assays with 1 Unit of PP-1 or PP-2A showed that the free 32 P released by PP-1 was much more prominent than PP-2A (Figure 2d).…”
Section: Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations